ELEVATING ELEMENTARY TEACHING COMPETENCE THROUGH COLLABORATIVE LEARNING WITHIN THE DAIRI ORGANIZED TRAINING SYSTEM - Jonson Rajagukguk; Arif Rahman; Sahala Siallagan; Osberth Sinaga (RADJA PUBLIKA, 2024)
To enhance the pedagogical skills of elementary school (SD) teachers in Dairi Regency, this study aims to evaluate the characteristics, feasibility, and effectiveness of the CarLOS-based training management model. Conducted from June 2023 to February 2024, the research involved 100 teachers and two model trials, utilizing the ADDIE framework—analysis, design, development, implementation, and evaluation. All research instruments were validated and tested for reliability through expert review and user trials. Key features of the CarLOS model include active participant engagement in collaborative design, adaptive flexibility to accommodate changes, collaborative learning that promotes cooperation and knowledge sharing, integration of technology-enhanced collaborative learning, a theoretical foundation combining inductive training and collaborative learning models, and inclusive participation to ensure broad involvement. Experts rated the model with an average score of 94%, while user trials yielded an 88.25% feasibility rating. Significant improvements in pedagogical competence were demonstrated by N-Gain scores of 76.08% in limited trials and 77.87% in extensive trials, supported by paired sample t-test results. With an overall user evaluation score of 94.49%, the findings confirm that the CarLOS model is highly effective in enhancing the pedagogical competencies of SD teachers in Dairi Regency. Beyond improving teaching skills, the model also strengthens the overall teaching methodology in primary education.